2015
DOI: 10.2500/ajra.2015.29.4194
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Olfactory Dysfunction and Suicidal Ideation: The Korea National Health and Nutrition Examination Survey

Abstract: In the Korean population, olfactory dysfunction was associated with an increased risk for depressed mood and suicidal ideation. Further epidemiologic and experimental studies are necessary to clarify the impact of olfactory dysfunction on psychological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…This was the first large population-based study to provide a clinical association between olfactory dysfunction and mental health [31] . To analyze the association between olfactory dysfunction and mental health such as depressive symptoms and suicidal thoughts in South Korea, using data from the 2010–2011 KNHANES, Joo et al found that the prevalence of olfactory dysfunction was 5.0% (ages ≥ 19 years) [32] .…”
Section: Major Population Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…This was the first large population-based study to provide a clinical association between olfactory dysfunction and mental health [31] . To analyze the association between olfactory dysfunction and mental health such as depressive symptoms and suicidal thoughts in South Korea, using data from the 2010–2011 KNHANES, Joo et al found that the prevalence of olfactory dysfunction was 5.0% (ages ≥ 19 years) [32] .…”
Section: Major Population Studiesmentioning
confidence: 99%
“…Essentially all studies show that the prevalence of decreased olfactory function increases very significantly with age [26, 32, 34, 36] . Which portion of the age range that is included in the study affects this phenomenon.…”
Section: Risk Factors That Have Been Associated With Olfactory Disordersmentioning
confidence: 99%
See 3 more Smart Citations